Penyelesaian Konflik Tanah Menggunakan Kearifan Lokal Ngadhu-Bhaga Di Kabupaten Ngada - Ferdinandus Bani; Fransiska Nyoman Supadi; Patrick. A. Yazakur; Stefanus Don Rade (Universitas Sains dan Teknologi Komputer, 2024)
Development the law of obligations and guarantees is related to local wisdom through the applications of norms related to vocal values and traditions. The development of engagement and guarantee concepts can reflect aspects of local wisdom, such as social values, culture or custom recognized in a particular community. By using normative research methods that focus on research that uses legal sources, statutory regulations and legal documents relating to wisdom in resolving land problems in the Ngadhu-Bhaga Community In Ngada Regency. Local wisdom of the Ngadhu-Bhaga Community In Ngada Regency, East Nusa Tenggara, land isssues are an important matter and are closely related to everyday life. In resolving land issues, the Ngadhu-Bhaga Community has methods in accordance with customs and cultural heritage that have been known for a long time.